Aprendizagem significativa do conceito de ressonância - Assis, Alice [UNESP]; Carvalho, Fernando Luiz de Campos [UNESP]; Amorim, Carlos Eduardo Silva de [UNESP]; Silva, Luciene Fernanda da [UNESP]; Silva, Luiz Guilherme Lucildo da [UNESP]; Dobrowolsky, Marcelo Schubert (My University, 2012)
In this research work we verified the interaction between teacher and students through the use of reading an alternative text, the use of an experimental activity demonstration and presentation of videos involving the concept of resonance in a room on the 3rd year of teaching medium, led to meaningful learning of that concept. The instruments for the creation of data were based on audio and video records, taken during the lecture and the written evaluations performed by the students two weeks later. The results showed that this interaction, mediated by the use of these resources, led to meaningful learning of the concept of resonance. It was also possible to observe the students' motivation to participate actively in class.

Nesta pesquisa verificamos se a interação entre o professor e os alunos, mediante a utilização da leitura de um texto alternativo, do uso de uma atividade experimental de demonstração e da apresentação de vídeos envolvendo o conceito de ressonância, em uma sala do 3º ano do Ensino Médio, propiciou a aprendizagem significativa do referido conceito. Os instrumentos para a constituição dos dados foram as transcrições das gravações, em áudio e vídeo, realizadas no decorrer da aula, bem como as avaliações escritas realizadas pelos alunos duas semanas depois. Os resultados mostraram que essa interação, mediada pela utilização das referidas estratégias, propiciou a aprendizagem significativa do conceito de ressonância. Também foi possível observar a motivação dos alunos em participarem ativamente da aula.
Meaningful learning of resonance
Keywords: Physics teaching; Meaningful learning; Resonance; Ensino de física; Aprendizagem significativa; Ressonância